TV Advertising Effectiveness and Profitability: Generalizable Results From 288 Brands. - Shapiro, Bradley T.; Hitsch, Günter J.; Tuchman, Anna E. (Econometrica, 2021)
We estimate the distribution of television advertising elasticities and the distribution of the advertising return on investment (ROI) for a large number of products in many categories. Our results reveal substantially smaller advertising elasticities compared to the results documented in the literature, as well as a sizable percentage of statistically insignificant or negative estimates. The results are robust to functional form assumptions and are not driven by insufficient statistical power or measurement error. The ROI analysis shows negative ROIs at the margin for more than 80% of brands, implying over‐investment in advertising by most firms. Further, the overall ROI of the observed advertising schedule is only positive for one third of all brands.